An overview of operations and processes for circular management of dredged sediments. (1st June 2022) - Crocetti, P.; González-Camejo, J.; Li, K.; Foglia, A.; Eusebi, A.L.; Fatone, F.
Graphical abstract: Highlights: Dredged sediments present increasing environmental, economic and social concerns. Sediments commonly present significant and variable concentrations of pollutants. Conventional sediment treatment has traditionally focused on pollutant removal. Circular Economy aims to reduce pollutants, reduce impacts and recover by-products. Circularity must overcome technical and sociopolitical barriers for its development. Abstract: Dredging is an essential technique to maintain proper water depths in ports and bays. Many dredged sediments are considered as toxic waste due to their significant amounts of metals and other pollutants. In consequence, they need to be treated to reduce this toxicity and avoid pollutant resuspensions. Physical operations and chemical, thermal and biological processes have been conventionally used to this aim, but the traditional linear sediment approach is often unsustainable and economically and environmentally demanding. Considering the increasing people's awareness in environmental issues, more efficient dredged sediment management schemes are required. Some authors are making significant efforts to improve circularity in sediment management processes by taking advantage of the mineral composition of sediments to obtain products for the building and road construction sectors, therefore decreasing the need of raw materials while reducing the amounts of sediments wasted to landfills. However, information related to the characteristics of these products, their mechanical behaviour and their functionality is still scarce, being sediment-based by-products developed mainly at low Technological Readiness Level (TRL), showing low global impact in the market. To implement circular economy in the dredged sediment sector, some technical and socio-political barriers must be still overcome. To this aim, further research and technological applications must be developed, with the support of decision makers and stakeholders. This review aims at giving an overview of the circular trends applied to toxic dredged sediment management, pointing at current opportunities, barriers and constraints that hinder its wide development.